ALIH KODE DAN CAMPUR KODE PADA NOVEL LAUT TENGAH KARYA BERLIANA KIMBERLY - Annisa Oktania Hasanah Annisa; Imam Safi’i (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
Abstract The purpose of this study is to describe the forms of code switching and code mixing in Berliana Kimberly's novel Laut Tengah. The type of research used in this research is qualitative by using a qualitative descriptive method. The results found in this study describe the existence of external and internal forms of code switching, mixing of external and internal code switching and the context behind the existence of code switching such as (1) speakers, (2) speech partners, (3) changes in situations and the presence of a third person, (4) Generating a sense of humor, (5) Just for prestige and the context behind the existence of code mixing, such as (1) Identification of varieties, (2) Identification of roles, (3) just to explain or interpret. The results found there were 27 outward code-switching forms, 1 inward code-switching form, 27 outward code-mixing forms and 23 internal code-mixing forms. Keywords: Code switching, Code mixing, background context